Thermal comfort in high altitude Himalayan residential houses in Darjeeling, India – An adaptive approach. Issue 1 (January 2020) - Thapa, Samar
The study of thermal comfort in buildings is required to maintain a stable and comfortable condition of the indoor environment. The climate chamber study used to determine thermal comfort is mathematically reproducible and robust, but exaggerative and hence is energy inefficient, whereas the adaptive model-based field survey method is exhaustive and bioclimatic specific. Although, several field survey-based thermal comfort studies have been reported from India, these studies were conducted mostly either in hot and humid or composite climatic condition, and very few research has been reported from cold climatic region, which lies mostly along the high altitudinal Himalayan region. In this paper, the results of field survey-based thermal comfort studies in residential houses of highly altitudinal Darjeeling Himalayan region in eastern India are presented. The study found that female subjects showed a lesser clothing cover but portrayed a higher discomfort with lower thermal sensation and higher comfort temperature. The comfort temperature as determined in this study did not comply with the ASHRAE standard 55 graphical method, and hence new comfort zone for regions with similar cold climate is proposed.